Aggregate effects of imperfect tax enforcement - Robles, Miguel (International Food Policy Research Institute, 2009)
This paper studies an economy in which the government is not able to perfectly enforce tax compliance among operating firms, and compares it with a similar economy but with perfect tax enforcement. I develop a competitive general equilibrium model where imperfect tax enforcement may affect aggregate outcomes through two mechanisms. First, it may distort firms' optimal output level as long as the probability of avoiding tax compliance is related to the firm's size. Second, poor tax enforcement may lead to a low provision of the public goods that complement firms' productivity. The results for a calibrated version of the model suggest that in economies with tax enforcement problems, aggregate output might be reduced by 12 percent. I also conclude that sizable aggregate effects can be obtained only when the public goods mechanism is at work.